Iliopsoas impingement after revision total hip arthroplasty treated with iliopsoas muscle transection. (May 2016) - Morohashi, Itaru; Homma, Yasuhiro; Kanda, Akio; Yamamoto, Yasuhiro; Obata, Hiroyuki; Mogami, Atsuhiko; obayashi, Osamu; Kaneko, Kazuo
Abstract: Introduction: Iliopsoas tendinitis after revision total hip arthroplasty (THA) is rare and its etiology and optimal treatment are still unclear. We report a case of iliopsoas impingement after revision THA with a Kerboull acetabular reinforcement device requiring two-level iliopsoas muscle transection. Presentation of case: A 70-year-old woman presented to our hospital complaining of debilitating right groin pain after revision THA with a Kerboull reinforcement device. She had undergone multiple hip operations after experiencing a pelvic fracture in a motor vehicle accident. A lidocaine nerve block at the level of the Kerboull device resulted in temporary but marked reduction in pain and a diagnosis of psoas impingent. We performed surgery via an anterior approach to release the iliopsoas muscle from the lesser trochanter. After iliopsoas tenotomy was performed, the muscle was still under high tension because of dense adhesions. Repeat transection of the iliopsoas muscle at the level of the anterior branch of the Kerboull device resulted in loosening of the iliopsoas muscle and resolution of impingement. Postoperatively, the patient's groin pain completely disappeared, and she can now walk with a single cane and is satisfied with her result. Discussion: Adhesions around the iliopsoas muscle likely contributed to the patient's groin pain. Open surgery to perform complete release of iliopsoas muscle impingement should be considered in patients with pain after revision THA. Conclusion: We reported a patient with Iliopsoas tendinitis after revision THA requiring two-level iliopsoas muscle transection. Highlights: We reported a patient with Iliopsoas tendinitis after revision THA. Two-level iliopsoas muscle transection was necessary. Open surgery should be considered in patients with pain after revision THA.